Improvement in Switching Characteristics and Bias Stability of Solution-Processed Zinc–Tin Oxide Thin Film Transistors via Simple Low-Pressure Thermal Annealing Treatment - Junhao Feng; Sang-Hwa Jeon; Jaehoon Park; Sin-Hyung Lee; Jaewon Jang; In Man Kang; Do-Kyung Kim; Jin-Hyuk Bae (Nanomaterials, 2023)
In this study, we used a low-pressure thermal annealing (LPTA) treatment to improve the switching characteristics and bias stability of zinc–tin oxide (ZTO) thin film transistors (TFTs). For this, we first fabricated the TFT and then applied the LPTA treatment at temperatures of 80 °C and 140 °C. The LPTA treatment reduced the number of defects in the bulk and interface of the ZTO TFTs. In addition, the changes in the water contact angle on the ZTO TFT surface indicated that the LPTA treatment reduced the surface defects. Hydrophobicity suppressed the off-current and instability under negative bias stress because of the limited absorption of moisture on the oxide surface. Moreover, the ratio of metal–oxygen bonds increased, while the ratio of oxygen–hydrogen bonds decreased. The reduced action of hydrogen as a shallow donor induced improvements in the on/off ratio (from 5.5 × 103 to 1.1 × 107) and subthreshold swing (8.63 to V·dec−1 and 0.73 V·dec−1), producing ZTO TFTs with excellent switching characteristics. In addition, device-to-device uniformity was significantly improved because of the reduced defects in the LPTA-treated ZTO TFTs.